Investigation of the Effect of Linalool on Carbon TetrachlorideInduced Oxidative Myocardial Injury in Male Rats - Ghasem Taraghy; Shiva Rahimi; Masoud Ojarudi; Aliakbar Fazaeli; Zeinab Namjoo; Lotfollah Rezagholizadeh (Journal of Mazandaran University of Medical Sciences, 2025)
Background and purpose: Cardiovascular diseases are among the leading causes of mortality worldwide, with myocardial injury often resulting from oxidative stress, drugs, and toxins. Linalool, a natural monoterpene alcohol found in various medicinal plants, has been reported to modulate oxidative stress. This study aimed to investigate the protective effects of linalool against oxidative myocardial damage induced by carbon tetrachloride (CCl ) in rats. Materials and methods: In this experimental study, 24 male Wistar rats were randomly divided into four groups of six (normal control, linalool control, injury group, and linalool pretreatment group). The first two groups received either physiological saline or linalool (25 mg/kg) for 14 days. The injury group was administered physiological saline for 14 days, followed by a single dose of 1 ml/kg of a 1:1 (v/v) olive oil and CCl mixture on the 14th day. The fourth group received linalool (25 mg/kg) for 14 days, followed by the same CCl mixture on day 14. Forty-eight hours after CCl administration, animals were anesthetized, and cardiac tissues were collected for biochemical and histopathological analyses. Results: The results showed that CCl significantly decreased the activity of antioxidant enzymes and total antioxidant capacity (P< 0.001), and increased malondialdehyde (MDA) levels compared to the control group (P< 0.001). Pretreatment with linalool significantly increased the antioxidant indices (P<0.001) and reduced MDA levels relative to the injury group (P<0.001). Furthermore, histopathological examination showed that linalool pretreatment mitigated CCl -induced structural alterations in myocardial tissue. Conclusion: Linalool effectively protects against CCl -induced myocardial oxidative damage by reducing lipid peroxidation, enhancing antioxidant capacity, and preserving cardiac tissue structure.